Basal glucocorticoid receptor activation induces proliferation and inhibits neuronal differentiation of human induced pluripotent stem cell-derived neuronal precursor cells. Issue 182 (September 2018) - Nürnberg, Elina; Horschitz, Sandra; Schloss, Patrick; Meyer-Lindenberg, Andreas
Graphical abstract: Highlights: Glucocorticoids (GC) are synthesized in neuronal precursor cells (NPCs). Basal GC and dexamethasone activate glucocorticoid receptors (GR) in NPCs. Activation of NPC-GR induces NPC proliferation and inhibits NPC differentiation. Inhibition of NPC-GR activity induces NPC neuronal differentiation. Abstract: Glucocorticoids (GC) have first been shown to originate from the adrenal glands where synthesis and release is controlled by the hypothalamic-pituitary-adrenal (HPA) axis. Recently, it was shown that GC and other steroid hormones are also synthesized in the central nervous system, so-called neurosteroids. GC bind to specific GC receptors (GR) which function as ligand-activated transcription factors. GR are expressed in nearly all cell types in the brain, and therefore GC have a strong impact on neuronal development. Most knowledge of the influence of GC on neurodevelopment has been obtained from animal research. Recent advances in stem cell technology made it possible to generate neuronal precursor cells (NPCs) and neurons from human induced pluripotent stem cells (hiPSCs). To explore the cellular mechanism of GC affecting human neuronal development, we quantified the proliferation and differentiation of hiPSCs–derived NPCs in the absence and presence of the selective high-affinity GR agonist dexamethasone and the selective GR antagonist mifepristone, respectively. Our results show that inhibition of GR significantly reduced proliferation of NPCs and promoted differentiation whereas GR activation suppressed neuronal differentiation. This implies that neuronal GC must be present in NPCs for proliferation. Consequently we identified the presence of 11-β-hydroxylase CYP11B1, which hydroxylates the respective steroid precursors to bioactive GC, in NPCs. We propose that hiPSC technology offers an ideal system to get more insight into the synthesising and regulatory pathways in steroidogenesis in human neurons and to differentiate between the mechanism by which adrenal GC and neuronal GC impact on neurodevelopment.